Ionizing radiation induces stem cell-like properties in a caspase-dependent manner in Drosophila. - Verghese, S.; Su, T.T. (PLoS Genetics, 2018)
Cancer treatments including ionizing radiation (IR) can induce cancer stem cell-like properties in non-stem cancer cells, an outcome that can interfere with therapeutic success. Yet, we understand little about what consequences of IR induces stem cell like properties and why some cancer cells show this response but not others. In previous studies, we identified a pool of epithelial cells in Drosophila larval wing discs that display IR-induced stem cell-like properties. These cells are resistant to killing by IR and, after radiation damage, change fate and translocate to regenerate parts of the disc that suffered more cell death. Here, we report the identification of two new pools of cells with IR-induced regenerative capability. We addressed how IR exposure results in the induction of stem cell-like behavior, and found a requirement for IR-induced caspase activity and for Zfh2, a transcription factor and an effector in the JAK/STAT pathway. Unexpectedly, the requirement for caspase activity was cell-autonomous within cell populations that display regenerative behavior. We propose a model in which the requirement for caspase activity and Zfh2 can be explained by apoptotic and non-apoptotic functions of caspases in the induction of stem cell-like behavior.